Digital Old Book Training to Support Learning in Islamic Boarding School (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Islamic boarding schools have an important role in organizing education in Indonesia. Historically, Islamic boarding schools are the oldest educational institutions that existed before Indonesia's independence. Based on research by the Ministry of Religious Affairs of the Republic of Indonesia, it is explained that Islamic boarding schools are the oldest education in Indonesia. This is certainly proof that its existence continues to exist and has a great contribution in educating the people. The role of Islamic boarding schools as educational institutions is of course to educate and teach students about various Islamic religious knowledge. Islamic boarding school learning has characteristics that continue to be preserved from time to time, including bandongan, sorogan, memorization, syawir and lalaran studies. Learning uses the bandongan system both in the morning and evening. In addition, learning activities are carried out in a classical manner followed by all students, both male and female. Of course, there are obstacles to this learning, including students being passive in participating in learning activities. This happens because the learning model focuses more on the transfer of knowledge rather than collaborative teaching learning which provides space for discussion and exploration of students' abilities and skills. Based on the problems faced by partners, it can be identified that partners have obstacles in two areas, namely 1) the absence of an effective and efficient yellow book learning method, 2) the absence of technology that can support yellow book learning. To solve the priority problem, training and workshop methods are used to improve the knowledge and skills of partners. The results of this community service activity are an increase in partner knowledge and can implement the technology of the Syamilah Mosque in learning the yellow book. The impact of implementing this technology is that learning is more effective and can increase the motivation of students to follow the learning of the yellow book. In addition, students are more participatory and active in learning activities because they can directly operate technology using computers.